A Cross-Cultural Grammar for Temporal Harmony in Afro-Latin Musics: Clave, Partido-Alto and Other Timelines - Vurkaç, Mehmet (Current Musicology, 2012)
This article presents an in–depth study of the musical concept called clave direction. The significance and regulative role of clave and similar cyclical timelines in Afro–Latin music have been established by many scholars, including Ned Sublette, Tomás Cruz, H.W. Soebbing, Rebecca Mauleón– Santana, and Ronald Herder. Clave is typically identified as the rhythmic anchor of Cuban music. Furthermore, Eugene Novotney, Hugo “Foca” Machado, Willy Muñoz, Jorge Sadi, and Chris Washburne, among other musicians and scholars, have argued that clave is central not only in Cuban music but in all Afro–American music. Although there is agreement on the importance of the concept, previous work has either been precise but culturally narrow in scope, or broad in scope but imprecise in its details. The present work builds on these earlier efforts to establish an understanding of clave direction that is precise, parsimonious (only two concepts suffice), and widely applicable. My analysis proceeds from the hypothesis that musics emerging from the transatlantic slave trade with significant Yorùbá influence share common traits including what has come to be called “clave.” Ruth M. Stone links observations of the musical role of clave–type patterns to the geographical origins of the patterns in West Africa, and emphasizes that this pattern–as– concept was brought to the Americas with the transatlantic slave trade. In particular, she states that clave “fits, of course, with other patterns played at the same time . . . Therefore, it has a role in keeping everything appropriately linked. Players use it as a reference point to synchronize the drum, bell, and vocal parts” (Stone 2005:81). D. A. Tobias has written that “the clave beat is the foundation of Latin–American rhythm and practically all of the other instruments are guided by this beat” (Tobias 1965:270). More recently, Arturo Rodriguez has argued that “clave is the key to understanding how Afro–Cuban music is arranged and flows” and that it is “a concept that is fundamental to Afro–Latin music” (Rodriguez 2003:41). Consequently, clave should be understood not only as a pattern but also as a critical musical concept.